2011
DOI: 10.1111/j.1540-8183.2009.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia following Percutaneous Coronary Intervention

Abstract: Judicious use of therapies that can cause thrombocytopenia, efficient detection of the cause of the decrease in platelet count, and appropriate management of the condition can potentially improve the quality of care and outcomes following PCI. Further research into risk factors that predispose post-PCI patients to developing thrombocytopenia is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…The ACUITY trial suggested patients with mild or moderate acquired thrombocytopenia had a three-fold higher incidence of non-CABG major bleeding, and those who developed severe acquired thrombocytopenia had a seven-fold higher rate of non-CABG major bleeding at 30-day follow-up [4]. However, in our study, the incidence of major bleeding was nearly the same (1.2% vs. clearance and low platelet count at admission has been previously described [22]. Potential mechanisms for thrombocytopenia in patients with renal dysfunction includes intrinsic platelet dysfunction, reduced platelet aggregation, and abnormalities in platelet-endothelial interactions [23].…”
Section: Independent Predictors Of Acquired Thrombocytopeniasupporting
confidence: 58%
See 1 more Smart Citation
“…The ACUITY trial suggested patients with mild or moderate acquired thrombocytopenia had a three-fold higher incidence of non-CABG major bleeding, and those who developed severe acquired thrombocytopenia had a seven-fold higher rate of non-CABG major bleeding at 30-day follow-up [4]. However, in our study, the incidence of major bleeding was nearly the same (1.2% vs. clearance and low platelet count at admission has been previously described [22]. Potential mechanisms for thrombocytopenia in patients with renal dysfunction includes intrinsic platelet dysfunction, reduced platelet aggregation, and abnormalities in platelet-endothelial interactions [23].…”
Section: Independent Predictors Of Acquired Thrombocytopeniasupporting
confidence: 58%
“…In this analysis, baseline creatinine clearance, baseline platelet count, and diabetes mellitus history emerged as independent clinical predictors of post‐PCI thrombocytopenia. The association of acquired thrombocytopenia with creatinine clearance and low platelet count at admission has been previously described . Potential mechanisms for thrombocytopenia in patients with renal dysfunction includes intrinsic platelet dysfunction, reduced platelet aggregation, and abnormalities in platelet–endothelial interactions .…”
Section: Discussionmentioning
confidence: 88%
“…8,9 TP either precedes ACS or is acquired during hospitalization and subsequent management. 10,11 In the latter case, TP is usually linked to drug-related adverse events 1214 or invasive procedures such as percutaneous coronary intervention (PCI) 15 and coronary artery bypass grafting surgery (CABG). 16 Indeed, a wide spectrum of complications has been described in patients with ACS that develop TP, which range from ischemic to bleeding adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Our case illustrates the importance of acknowledging different diagnostic possibilities when thrombocytopenia develops after PCI, even when heparin is potentially involved (Table 1) [1]. Although HIT type 2 was considered, the very low platelet count, concomitant contrast exposure, and absence of thrombosis yielded a 4 T’s score of only 3.…”
Section: Discussionmentioning
confidence: 84%